Orthodontics on sale: fixed appliances on E-commerce platforms - Kamarudin Yasmin; Zakaria Nor Nadia; Xinhui Violette Ong (Sciendo, 2022)
The sale of orthodontic materials, considered as medical devices, is regulated in order to protect patients. The availability of orthodontic products on e-commerce platforms, however, may go unregulated and compromise patient safety.